2020
DOI: 10.1039/d0dt00283f
|View full text |Cite
|
Sign up to set email alerts
|

ESI MS studies highlight the selective interaction of Auranofin with protein free thiols

Abstract: The study of the mode-of-action of Auranofin, a cytotoxic gold(i) compound, reveals that it binds exclusively to the free and solvent-accessible cysteine residues of biologically relevant proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 55 publications
(69 reference statements)
4
57
0
Order By: Relevance
“…Thus, we performed ESI-MS experiments also for AF and AF-I incubated with the two latter amino acids. Results confirmed the lack of reactivity for these two target molecules with AF and AF-I, further supporting the findings already published by some of us regarding the reactivity of auranofin and its derivatives toward protein targets (Landini et al, 2017;Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Esi Mass Spectrometrysupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, we performed ESI-MS experiments also for AF and AF-I incubated with the two latter amino acids. Results confirmed the lack of reactivity for these two target molecules with AF and AF-I, further supporting the findings already published by some of us regarding the reactivity of auranofin and its derivatives toward protein targets (Landini et al, 2017;Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Esi Mass Spectrometrysupporting
confidence: 90%
“…Starting from our previous findings on the reactivity of AF and its analogs toward protein targets (Pratesi et al, 2014(Pratesi et al, , 2018Marzo et al, 2017Marzo et al, , 2019Cirri et al, 2019;Zoppi et al, 2020), here we have extended the investigation-at the molecular levelon the mode of action of these medicinally relevant gold(I) compounds. Specifically, we have focused our attention on AF and its analog where the thiosugar moiety is replaced by the iodide ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the adopted experimental strategy was as follows. All four gold complexes were challenged with HSA, hCA I, and the TrxR dodecapeptide according to a well-established experimental protocol (Tamasi et al, 2014;Marzo et al, 2017Marzo et al, , 2019Michelucci et al, 2017;Pratesi et al, 2018;Ferraro et al, 2020;Zoppi et al, 2020). Different times and stoichiometries were explored to identify the best conditions to obtain adduct formation and to improve the quality of the ESI MS spectra.…”
Section: The Panel Of Gold(iii) Complexes and The Investigative Strategymentioning
confidence: 99%
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%